Occurrence of PBDEs and alternative halogenated flame retardants in sewage sludge from the industrial city of Guangzhou, China. (January 2017) - Wu, Qihang; Li, Haiyan; Kuo, Dave T.F.; Chen, Shejun; Mai, Bixian; Li, Huosheng; Liu, Zhineng; Deng, Mingjun; Zhang, Haozhi; Hu, Xiaodong; Geng, Xinhua; Chen, Yongheng
Abstract: This study investigated the prevalence and abundance of halogenated flame retardants (HFRs) in sludge samples from 5 sewage treatment plants in Guangzhou, China. Detection of 18 polybrominated diphenyl ethers (PBDEs), 9 alternative HFRs including Dechlorane Plus (DP), brominated alkylbenzenes, and polybrominated biphenyls, and 2 related degradation products was conducted. Decabromodiphenyl ether (BDE 209) and decabromodiphenyl ethane (DBDPE) were the dominant HFRs, with concentrations ranging from 200 to 2150 ng/g and 680–27, 400 ng/g, respectively. The DBDPE detected was the highest level reported so far, exceeding those previously reported by 10–100 times. PBDEs were surpassed as the dominant HFRs in sewage sludge, with mean DBDPE/BDE 209 ratio exceeding 2 in all samples. The review of earlier surveys reveals that DBDPE level was surging while BDE 209 was declining. Annual emissions of BDE 209, DP, and DBDPE were estimated to be 227.9, 10.5, and 979.3 kg/yr, respectively. Although ecological risks assessment suggested low risks for the examined sludge, the key environmental properties and transformation pathways of alternative HFRs remain largely unknown. These findings prompt for further investigations on alternative HFR and sustainable management practices for HFR-laden biosolids. The HFR emission pattern revealed in this study is likely representative of other similarly industrialized regions in the post-PBDE era. Graphical abstract: Highlights: Decabromodiphenyl ether (BDE 209) and decabromodiphenyl ethane (DBDPE) were the dominant HFRs in sewage sludge. DBDPE level appeared to be increasing while BDE 209 was declining in sludge samples of Guangzhou. Annual emissions of BDE 209, DP, and DBDPE were estimated to be 227.9, 10.5, and 979.3 kg/yr, respectively.